Bold & Beautiful: Public Sex & Kink Erotica - Stigsdotter, Saga (Saga Egmont, 2023)
\'Bold & Public Sex & Kink Erotica\' from LUST is a collection of steamy stories for readers who find pleasure in kinks, public sex, exhibitionism, voyeurism, watching, and being watched. From bondage to swinging, from elicit encounters in public places to sex clubs, there\'s something to excite every reader.